Animal Subjugation and Human Disgrace: Power and Violence in Coetzee’s Disgrace - Dr. M. Bhuvaneswari; Dr. A. Desiree Ann; Dr. K. Yesodha Devi (The Bioscan, 2024)
In this paper we examine how J.M. Coetzee’s Disgrace exposes the failure of traditional power structures through the personal collapse of David Lurie, a white academic whose authority unravels after he exploits a student. The novel combines sexual misconduct, institutional failure, and post-apartheid racial dynamics into an extensive critique of human entitlement. As Lurie begins working in an animal clinic, his encounters with voiceless, dying dogs reveal an ethical realm outside language and control. The care he extends to animals—though it offers no redemption—marks a shift from dominance to humility. The novel shows a strong connection between the fall of human power and the ignored suffering of animals. It suggests ethical awareness emerges not from authority but from the capacity to witness and bear pain without defence.